2019
DOI: 10.1002/qj.3706
|View full text |Cite
|
Sign up to set email alerts
|

A physically based precipitation separation algorithm for convection‐permitting models over complex topography

Abstract: A new algorithm is described that can separate precipitation output from convection‐permitting models into three different types of precipitation: (a) convective, (b) stratiform, and (c) orographically enhanced precipitation. The algorithm is based on physical processes that underlie these types of precipitation and it is applicable over both ocean and land surfaces. It is particularly well suited for mountainous areas or other regions exhibiting complex terrain. The algorithm's performance is first demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 31 publications
(54 reference statements)
0
29
0
Order By: Relevance
“…These systems need to be better described, both their identification procedure and physical meaning. There is a recent paper by Poujol et al (2020) on a separation between convective and stratiform precipitation. It might be interesting to check if the precipitation within high pressure systems can be classified as convective using their approach.…”
Section: Interactive Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…These systems need to be better described, both their identification procedure and physical meaning. There is a recent paper by Poujol et al (2020) on a separation between convective and stratiform precipitation. It might be interesting to check if the precipitation within high pressure systems can be classified as convective using their approach.…”
Section: Interactive Commentmentioning
confidence: 99%
“…We thank the reviewer for pointing us to the paper by Poujol et al (2020), as their classification approach looks very promising. However, we do not think that it would add much to the characterization of the high-pressure area precipitation, because it is fairly obvious to us (from extensive visual analysis of precipitation fields during method development) that most of this precipitation is convective.…”
Section: Interactive Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the global mean, precipitation is expected to increase at a rate of 2 % per degree of global-mean warming, but changes in short-term precipitation are likely to occur at much faster rates (Trenberth, 1999;Held and Soden, 2006;Schneider et al, 2010). In the last decade, huge progress has been made in realistically simulating the hydrological cycle with highresolution climate models, including the spatial distribution of precipitation, its diurnal cycle, and the statistics of extreme events (e.g., Hohenegger et al, 2008;Kendon et al, 2012;Ban et al, 2014Ban et al, , 2015Prein et al, 2015;Clark et al, 2016; S. Rüdisühli et al: Attribution of precipitation to cyclones and fronts over Europe Keller et al, 2016;Leutwyler et al, 2017). A major part of this progress is due to the step change of simulating deep convection explicitly instead of using a parameterized representation.…”
Section: Introductionmentioning
confidence: 99%
“…A major part of this progress is due to the step change of simulating deep convection explicitly instead of using a parameterized representation. In their systematic comparison of climate model simulations with parameterized or explicit convection, Prein et al (2015) found that "Improvements [when using explicit convection] are evident mostly for climate statistics related to deep convection, mountainous regions, or extreme events. "…”
Section: Introductionmentioning
confidence: 99%